Evaluasi Pembelajaran Berbasis Proyek Pada Materi Bangun Ruang Kelas V Sekolah Dasar Dengan Model CIPP - Agung Wibowo; Dian Armanto; Wildansyah Lubis (Journal of Educational Analytics, 2022)
The results of the assessment using CIPP as a decision. Evaluation decisions for the application of learning. This study aims to provide an assessment of project-based learning on classroom construction material for class V SDN 250 Sinar Gading II. Implementation of research with a qualitative approach by applying the CIPP evaluation model. Implementation of the overall evaluation of the aspects of context, input, process, and output of results/products to assess the effectiveness of project-based learning. The subjects were teachers and fourth grade students at SDN 250 Sinar Gading II. The data were obtained by primary and secondary observations and the data were analyzed and described. The overall project-based learning on the material for the V grade students of SDN 250 Sinar Gading II was very good.